Decent and fair damages against owner of land rights in land procurement for development for public interest - Mulyadi; Made Warka; Sri Setyadji (Technium Social Sciences Journal, 2021)
This study uses normative research methods. The concept of appropriate and fair compensation for the owner of land rights in Land Procurement for the development of the public interest.The party entitled to receive compensation is obliged to relinquish rights and submit proof of control or ownership of the Land Procurement Object to the Agency that requires the land through the Land Agency